Transcendence and Sensoriness: Perceptions, Revelation, and the Arts - Christoffersen, Svein Aage (Studies in Religion and the Arts Ser., 2015)
In Transcendence and Sensoriness, scholars of theology, philosophy, art, music, and architecture, discuss questions of transcendence, the human senses, and the arts through case studies considered in a broad theological framework of religious aesthetics of the arts.